Faktor-Faktor yang Berhubungan dengan Kunjungan Posyandu Pada Balita - Nikmah Jalilah Ritonga; Dwi Handayani; Kardina Hayati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Factors that affect the low visit of mothers under five to the posyandu include the mother's age, mother's education, mother's knowledge, mother's occupation, and distance from home to posyandu (Kusmayanti, 2017). This study aims to determine the factors associated with visits to the toddler posyandu. Respondents in this study were mothers who had toddlers. The number of samples in this study were 40 people. The results of the statistical test using the Chi-Square at the 95% confidence level (? = 0.05) obtained a p value 0.05, which means that there is a significant relationship between knowledge, education, work and distance from home to the posyandu with visits to the toddler posyandu in Sungai Besar Village in 2025.